Homomorphic Encryption: Privacy Preserving Amicable E-voting System - Patel, Bhumika; Bhatti, Dharmendra (International Journal of Computer Sciences and Engineering, 2019)
Advancement in technology plays a vital role in adherence of democratic processes. While making technology encroachment, democratic nation smoothens to the process of e-voting for civilians. Compromising security is an adverse effect in progression of online easy going processes. Trust and privacy are at risk especially in online vote storage. One way to protect stored data is to apply encryption with the condition that only recipient can decode those data. This technique can be carried out with online electronic voting system to prevent vote tampering from insider or outsider adversaries. This research has been carried out to achieve privacy preservation and increasing trust factor among voters. To achieve given objective various additive Homomorphic encryption algorithms are implemented and as a result proved that paillier’s Homomorphic encryption is the effective algorithm to be implemented to accomplish privacy on casted votes.